Utilization of tissue culture techniques for the conservation and international exchange of cassava (Manihot esculenta) germplasm - Roca, W.; Narvaez, J; Rodríguez, J.; Reyes, R.; Mafla, G.; Beltrán, J.; Roa E, Julio César; Ramírez, H.; Rodríguez, A.M. (International Center for Tropical Agriculture, 1981)
With graphs, illustrations, photos, and tables, the utilization of tissue culture techniques for the conservation and international exchange of cassava is briefly described. Likewise, the results of the phenotypic stability of cassava cv. M. Mex 20, M. Col 650, M. Col 2197, CM 305-38, and CM 323-375, stored under min. growth culture conditions for 42, 12, 18, 30, and 30 mo., resp., are given. To evaluate the phenotypic stability, morphological, agronomic, and biochemical parameters were considered. With the exception of variation in the color of root epidermis and cortex, no changes resulted solely from in vitro storage in any of the morphological, agronomic, and biochemical characters evaluated. Finally the use of a modified Murashige and Skoog medium, supplemented with GA, thiourea, and sucrose, to achieve embryo germination and plant development in 10 wild Manihot spp., is reported. (CIAT)